The Evaluation of Water Quality Parameters of BeydilliRiver(Hafik-Sivas) - Mutlu, Ekrem; Kutlu, Banu; Demir, Tuğba; Yanık, Telat; Sutan, Nicoleta Anca (Journal of Selçuk University Natural and Applied Science, 2014)
parameters of Beydilli River rising from foots of Karakis Mountain constituting the border of Gülpınar Village located in Hafik district of Sivas and Kızılalan Village being affiliated with central district of Sivas city, passing through Karabalçık, Beydilli, Bayıraltı and Düzyayla villages, mixing with Horohon Brook, and satisfying the drinking and usage water needs of Karabalçık and Beydilli villages, also being used in watering agricultural lands. It has also been aimed to create a database to be used in further studies on Beydilli River on which there has never been carried out any study. The study has been started in March 2011. Among the water quality parameters, the dissolved oxygen (DO), pH, temperature, saltiness, electrical conductivity (EC), suspended solid matter (SSM), chemical oxygen demand (COD), biological oxygen demand (BOD), total ammonic azote, nitrite, nitrate, total alkalinity, total hardness, phosphate, sulfate, sulfite, sodium, magnesium, calcium, ferrous, lead, copper and cadmium analyses have been carried out monthly for 12 months through sampling from 7 sampling stations. As a result of this study, it has been determined in which quality category Beydilli River’s water belongs to according to SWQMR, and it has been discussed whether or not the actual situation of water quality is suitable for aquacultural activities.
Keywords: Water pollution, Water quality, BeydilliRiver, Sivas